Karjanlanta kasvien fosforin lähteenä - Kaila, Armi (Agricultural and Food Science, 1950)
The organic phosphorus in farm manure seems as such to be unavailable for plants. Therefore, the value of manure as a phosphorus fertilizer largely depends on the rapidity with which the mineralization of its organic phosphorus takes place. In fermenting manure the decomposition of organic phosphorus compounds will become more effective than their microbiological synthesis as soon as the amount of its organic phosphorus (P) exceeds circa 0.2 per cent of the manure dry matter (9). From thence a continual increase in the relative amount of inorganic phosphorus can be detected, until about 70 per cent of the total phosphorus occurs in inorganic form (8, p. 72). The largest part of the remaining organic phosphorus does not dissolve in ethanol, in water, or in N/2 hydrochloric acid, probably representing nucleic acid derivatives, or organic phosphorus combined with proteines (8). An incubation experiment performed with this insoluble residue of fractionation of a manure sample indicated a relatively slow mineralization of its phosphorus (Table 1). Addition of inorganic phosphorus and glucose in order to stimulate the microbiological activity did not remarkably increase the mineralization. No mineralization of the phosphorus in this fraction was found to take place in soil, neither any reliable increase in inorganic phosphorus could be detected when samples of manure were incubated in soil (Table 2). The technique used in these laboratory experiments was similar to that developed by Bower (2) and Pearson et. al. (11), except that instead of 1 N sulfuric acid 4 N sulfuric acid was used in extraction, because the latter was found to give relatively reliable results even when acid soils were in question (p. 110). Difficulties in the determination of changes in manure phosphorus in soil without the help of radioactive phosphorus were discussed. Since the mineralization of the in water and in N/2 hydrochloric acid insoluble organic phosphorus of manure seems to occur in soil very slowly, this fraction may not represent any available phosphorus source for plants, at least not during the first summer. The soluble organic phosphorus was found to be available food for microorganisms, and this was taken to mean that this fraction of manure phosphorus may take part in the active phosphorus cycle in soil. It has been claimed that the manure phosphorus does not become fixed by soil as rapidly as inorganic phosphates, and that it thus remains more available for plants than the latter (16, 18).This may be explained by the facts that the soluble humates of manure compete with phosphate anions for the exchange position of the adsorbing soil complex, or that the manure comes into soil in pieces which decrease the contact between manure phosphorus and soil particles. Results obtained from experiments where soil was shaken in water extract of manure and in potassium phosphate solution (Table 3), and where the solubility of the adsorbed phosphorus was determined (Table 4), did not indicate any protective action of soluble manure organic matter against the fixation of phosphorus by soil. Nor did manure increase the phosphorus concentration of soil extract more than superphosphate when equal amounts of soluble inorganic phosphorus in form of manure or of superphosphate were shaken with soil in water (Table 5). The adsorption of phosphorus on slightly acid soils seemed to be less efficient when samples of fermented manure were incubated with soil, and the amounts of water-soluble and N/2 acetic acid-soluble phosphorus determined in fresh samples taken at different intervals (Table 7). This proves how the occurrence of manure in lumps or pieces protects its phosphorus against fixation by soil. The acid soils seemed to fix even the manure phosphorus very efficiently, apparently owing to the rapid fixation by sesquioxides during extraction. Successive extractions of soil and of soil with manure (Table 6) showed that manure may be able to maintain for a short period a rather constant concentration of inorganic phosphorus, but that before long its remaining phosphorus becomes firmly fixed. Not only the solubility of manure phosphorus, but also its availability for plants was found to decrease on account of incubation in soil (Table 8). Owing to the fact that the difficultly soluble or insoluble organic phosphorus in farm manure seems to mobilize in soil very slowly, only the inorganic and perhaps the easily soluble organic phosphorus can be taken into consideration when the estimation of manure as a phosphorus fertilizer is in question. In Finnish farm manure there is, on the average, only 0.19 per cent P2O5 and about 60 per cent of it may occur in inorganic form (8). If the amount of soluble organic phosphorus, corresponding in fermented manure approximately 10 per cent of total phosphorus, is included, it can be calculated that 20 tons of farm manure contains about 25 kg. of available or easily mobilizable P2O5. Therefore, in order to provide phosphorus for maximum plant growth it is nearly always necessary to apply mineral phosphate fertilizers in addition to our farm manure.